KUALITAS PAPAN LAMINA DENGAN PEREKAT RESORSINOL DARI EKSTRAK LIMBAH KAYU MERBAU - Adi Santoso; Gustan Pari; Jasni (Jurnal Penelitian Hasil Hutan, 2015)
Polyphenol chemical components extracted from merbau (Intsia spp.) wood exhibit a strong affinity for resorcinol and formaldehyde in alkaline conditions, forming a copolymer that could serve as an adhesive. This paper studies the use of resorcinol adhesives from merbau wood extracts containing poly phenolics which copolymerize with formaldehyde bonding wood laminates. Results show that copolymer of merbau extracts with formaldehyde could produce resin with molecular weight 49,658. The resin can be used as adhesive for laminated board manufacturing of a 3 ply-1 strip flooring parquet constructed with 7 wood species, i.e: sungkai, karet, kempas, merbau, mangium, mahoni and sengon. Bonding quality and physical-mechanical properties of the products laminated meet the same product that glued using imported adhesive and included exterior quality with E₀ or F**** types of low emission formaldehyde.